Institutional Change and Power Asymmetry in the Context of Rural India - Patnaik, Amar (SpringerLink Bücher, 2019)
This book explains how to bring about institutional change and foster new institutional structures (institution building) by resolving power inequities in a rural ecosystem in India, and advocates the identification of an appropriate institutional champion to make this happen. The book develops a power-asymmetry-based framework and argues that a champion with the right attributes and the 'ability’ to 'convene' people over a social issue can only succeed if he/she can resolve or reduce the deep-rooted societal power asymmetries within that community. It also presents four case studies that indicate how such social change is typically spread over a long period of time